## Factoring and Simplifying the Expression (x^3 + 125) / (x + 5)

This expression involves a cubic polynomial in the numerator and a linear term in the denominator. To simplify it, we can use the concept of **factoring** and **canceling out common factors**.

### Recognizing the Pattern

The numerator, x^3 + 125, is a sum of cubes. This is because 125 is the cube of 5 (5 * 5 * 5 = 125). We can use the following formula to factor a sum of cubes:

**a^3 + b^3 = (a + b)(a^2 - ab + b^2)**

In our case, a = x and b = 5. Applying the formula, we get:

**x^3 + 125 = (x + 5)(x^2 - 5x + 25)**

### Simplifying the Expression

Now we can substitute this factored form back into our original expression:

(x^3 + 125) / (x + 5) = [(x + 5)(x^2 - 5x + 25)] / (x + 5)

Notice that we have a common factor of (x + 5) in both the numerator and denominator. We can cancel this out:

[(x + 5)(x^2 - 5x + 25)] / (x + 5) = **x^2 - 5x + 25**

### Result

Therefore, the simplified form of the expression (x^3 + 125) / (x + 5) is **x^2 - 5x + 25**. This expression is valid for all values of x except for x = -5, where the original expression is undefined.